Design of Control System for Weighbridge Gate at PT. Sido Agung Agro Prima - Soleh, Muhamad (Electrical Engineering Departement, Faculty of Engineering, Universitas Swadaya Gunung Jati, 2025)
Sido Agung Agro Prima has a consideration problem that is transported by trucks on the weighbridge, errors often occur in weighing because the weighing process has not been completed, the next car enters during the weighing process, so the weight that is weighed is inaccurate, this causes losses to the company because the tonnage weight is too high. excess. A prototype tool has been designed to weigh the mass of objects using the HX711 Sensor (Load Cell). The circuit used consists of Power Supply, Loadcell, HX711, ATMega 328, LCD, Buzzer. The way this tool works is when the vehicle is detected on the ultrasonic sensor, then the load cell is prepared to weigh and the weight of the vehicle is detected by the load cell with the output signal in analog form which will be sent to the hx711 sensor module to convert the output signal to digital with parallel communication which is then sent to the arduino microcontroller as the control center then the LCD displays the weight of the vehicle and the level of violation if there is an overload of the load cell, if during the weighing process there is a violation of the weight of the load that has been determined by the officer then an alarm will sound. The results of several prototype tests work according to instructions and according to the Arduino program that has been made and this tool works automatically by responding to how much mass the object is detected by the sensor. Arduino-Uno then processes the mass of the object and gives an output that has been programmed previously with an error percentage of 0.107% which is then displayed on the LCD.